2019
DOI: 10.1038/d41586-019-02687-1
|View full text |Cite
|
Sign up to set email alerts
|

Treading the tightrope of opioid restrictions

Abstract: Efforts to restrict opioid prescriptions in the United States are having unintended effects on people with chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It seems that clinicians were increasingly aware of the potential harm of opioids, which led to reduced daily MME below 50. Although there is no widely accepted guideline for opioid prescription among metastatic breast cancer patients, there are many studies in the literature on other populations that suggested that daily dosages above 50 MME is associated with higher risk for opioid overuse, which led the Centers for Disease Control to recommend clinicians carefully reassess evidence of individual benefits and risks when considering increasing dose to > 50MME per day and avoid prescribing > 90MME per day in 2016 22 . Although this did not apply specifically to people with cancer, this opioid threshold was adopted by some regulatory organizations and insurance companies, therefore potentially impacting the prescribing habits of clinicians 22 .…”
Section: Discussionmentioning
confidence: 99%
“…It seems that clinicians were increasingly aware of the potential harm of opioids, which led to reduced daily MME below 50. Although there is no widely accepted guideline for opioid prescription among metastatic breast cancer patients, there are many studies in the literature on other populations that suggested that daily dosages above 50 MME is associated with higher risk for opioid overuse, which led the Centers for Disease Control to recommend clinicians carefully reassess evidence of individual benefits and risks when considering increasing dose to > 50MME per day and avoid prescribing > 90MME per day in 2016 22 . Although this did not apply specifically to people with cancer, this opioid threshold was adopted by some regulatory organizations and insurance companies, therefore potentially impacting the prescribing habits of clinicians 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Two veterans [VET01, VET03] , however, provided negative feedback regarding the VA health system, and one veteran [VET01] blamed the VA for his addiction to opioids by being over-prescribed painkillers. Although recent research claims a decline in long-term prescription opioid use [ 38 ], opioids have long been over-prescribed for recovery after surgical procedures [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important limitation of our study is that the consumption patterns of opioid-exposed patients were not examined. This is a pervasive problem in surgical opioid literature: most existing post-surgical opioid prescribing research applies to opioid-naive patients only 15 , 23 . Treating the post-surgical pain of opioid-exposed patients is a space largely left up to clinical intuition.…”
Section: Discussionmentioning
confidence: 99%
“…This is a pervasive problem in surgical opioid literature: most existing post-surgical opioid prescribing research applies to opioid-naive patients only. 15,23 Treating the postsurgical pain of opioid-exposed patients is a space largely left up to clinical intuition. Moreover, while our results undoubtedly expose potential areas of under-prescribing, some findings of the current study, including procedure-specific patterns, may not be generalizable to all patient populations, as the current study utilizes consumption data from a single institution.…”
Section: Limitationsmentioning
confidence: 99%